2010
DOI: 10.1016/j.jacc.2009.11.034
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous Pacemaker and Implantable Cardioverter-Defibrillator Lead Extraction in 100 Patients With Intracardiac Vegetations Defined by Transesophageal Echocardiogram

Abstract: Patients with intracardiac vegetations identified on transesophageal echocardiogram can safely undergo complete device extraction using standard percutaneous lead extraction techniques. Permanent devices can safely be reimplanted provided blood cultures remain sterile. The presence of intracardiac vegetations identifies a subset of patients at increased risk for complications and early mortality from systemic infection despite device extraction and appropriate antimicrobial therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
104
0
11

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 133 publications
(116 citation statements)
references
References 44 publications
1
104
0
11
Order By: Relevance
“…10,66,70,[74][75][76] In most of these studies, more than 90 % of patients underwent complete CIED removal. Mortality with endocarditis is reported between 24.5 % and 29.0 %, 31,71,77 and CIED infections with endocarditis have a higher mortality than pocket infection. 3,78 One study found a 6-month mortality of 10.1 % after system removal in patients with small lead vegetations and 18.4 % in patients with large lead vegetations.…”
Section: Outcomes Of Cardiac Implantable Electronic Device Infectionmentioning
confidence: 98%
“…10,66,70,[74][75][76] In most of these studies, more than 90 % of patients underwent complete CIED removal. Mortality with endocarditis is reported between 24.5 % and 29.0 %, 31,71,77 and CIED infections with endocarditis have a higher mortality than pocket infection. 3,78 One study found a 6-month mortality of 10.1 % after system removal in patients with small lead vegetations and 18.4 % in patients with large lead vegetations.…”
Section: Outcomes Of Cardiac Implantable Electronic Device Infectionmentioning
confidence: 98%
“…Staphylococcal infections dominate the responsible flora. In a recent survey Methicillinsensitive S. aureus was found in 25% Methicillin-resistant S. aureus was found in 34% and Coagulase-negative S. species were found in 14% of the cases of pacemaker endocarditis [21]. It should be noted that even if the infection is by clinical examination found to be confined to the pocket of the device, complete removal of the system including the leads has to be performed in order to avoid future relapse of the disease in the form of endocarditis.…”
Section: Indications For Lead Extractionmentioning
confidence: 95%
“…Although a clear cut-off point for the vegetation size has not been defined, many physicians would advocate surgical removal of leads of infected leads with large vegetations (>1-1,5 cm) [32], [33]. More recent evidence, however, suggests that even larger vegetations can be safely removed percutaneously [21]. Laboratory examinations should include: blood typing and crossmatch, a full blood count, coagulation profile, electrolytes, renal and liver function tests, virology screen (Hep B, C and HIV), Creactive protein and erythrocyte sedimentation rate.…”
Section: Pre-procedural and Patient Preparationmentioning
confidence: 99%
“…vegetations identifies a subset of patients at increased risk for complications and early mortality from systemic infection despite device extraction and appropriate antimicrobial therapy (Grammes et al, 2010).…”
Section: Complications Of Pacemaker Implantation 275mentioning
confidence: 99%